Assessment of the warehouse receipt system for agricultural commodities in Indonesia - Gunawan, Endro; Kuwornu, John K. M.; Datta, Avushek; Loc, Thai Nguyen; Indonesian Agency for Agricultural Research and Development (IAARD) (Pathum Thani, Thailand : Asian Institute of Technology, 2019)
The common problem in agricultural commodity is price volatility. The warehouse receipt system is one of the means by which the farmers can manage the price volatility and finance their production activities. The warehouse receipt system has been implemented in Indonesia in 2006 based on Law No. 9 of 2006. As a new financial system, warehouse receipt system is not well known and not fully understood by stakeholders. Consequently, the warehouse receipt system has been under-utilized by farmers as they are reluctant to use it. This study examined the role of the warehouse receipt system for agricultural commodities in Indonesia. Specifically, the objectives of the study were: (a) to assess the farmers{u2019} perceptions of the warehouse receipt system, (b) to determine the factors influencing farmers{u2019} use of the warehouse receipt system, and (c) to evaluate the factors influencing farmers{u2019} use the private and public warehouses. The locations of this research were the Subang and Cianjur districts in West Java Province in Indonesia. Primary data were collected from 500 farmers, 12 warehouse operators and 4 local government officers in the districts, through questionnaire administration. The weighted average index was used to assess the farmers{u2019} perceptions regarding the warehouse receipt system. Binary logit regression was employed to examine the factors influencing farmers{u2019} use of the warehouse receipt system. Binary and bivariate probit regressions were employed to determine the factors influencing farmers{u2019} choice of use of private and public warehouses. The result of the weighted average index revealed that there was a strong perception that the warehouse receipt system is not well known and provides easy access to credit, but smallholder farmers have limited access. Moreover, there was a weak perception that the warehouse receipt system has complicated regulations and slow in issuing the warehouse receipt. The main problems of the warehouse receipt system were lack of awareness, lack of human resources for management, and limited access for smallholder farmers. The result from the binary logit regression revealed age, land ownership, selling price, availability of credit, and availability of transportation facilities positively influenced the decision to use the warehouse receipt system, whereas education, income per annum, profit and participation in farmers{u2019} group negatively influenced the decision of farmers to use the warehouse receipt system. The bivariate probit regression was used to check if there is endogeneity problem in farmers{u2019} use of the public and private warehouses. The results revealed that the farmers use one type of warehouse (i.e. public or private). Therefore, there is no endogeneity problem in this case, and this implies that individual binary probit regressions of the farmers{u2019} use of private and public warehouses are appropriate. The results of binary probit regression revealed that profit, availability of insurance and availability of processing facility positively influenced the farmers{u2019} decision to use private warehouse receipt system, whereas education, production, selling price and distance from the farm to the warehouse negatively influenced farmers{u2019} decision to use the private warehouse receipt system. Also, age, education, selling price and distance from the farm to the warehouse positively influenced the farmers{u2019} decision to use the public warehouse receipt system, whereas availability of processing facility negatively influenced the decision of farmers to use the public warehouse receipt system. The implications and policy recommendations are provided.
A Dissertation submitted in partial fulfillment of the requirements for the Degree of Doctor of Philosophy in AgriBusiness Management
Thesis (Ph.D.) - Asian Institute of Technology, 2019
Keywords: Warehouse receipts -- Indonesia; Farmers -- Indonesia -- Attitudes